Unemployment in Ukraine: an Analysis of the Dynamics, Gender, Age Structure and Causes of Unemployment - S. CHERVONA (Naukovij Vìsnik Nacìonalʹnoï Akademìï Statistiki, Oblìku ta Auditu, 2020)
The article examines the dynamics of the number of registered unemployed and unemployed in the definition of the International Labor Organization (ILO), as well as the levels of these indicators. It is determined that compared to 2010, the largest increase in the number of registered unemployed could be observed in 2011. The most significant decrease in the studied indicator during the entire research period, both compared to 2010 and the previous year, was in 2017. In 2018–2019, the number of registered unemployed continued to decline. The increase in the registered unemployment rate compared to 2010 was in 2011, 2013–2016, and a significant increase in the level of the studied indicator was recorded in 2015. The decrease in the studied indicator was recorded in 2012 compared to 2011, as well as in the last four years of the research period.